2009
DOI: 10.1016/j.tetlet.2009.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective synthesis of the C1–C12 segment of iriomoteolide-1a: a very potent macrolide antitumor agent

Abstract: A stereoselective synthesis of the C 1 -C 12 segment of the potent cytotoxic macrolide, iriomoteolide 1a, has been accomplished. The key steps involve an enzymatic kinetic resolution of a β-hydroxy amide, a Pd-catalyzed cross-coupling to a substituted allylsilane, a highly regio-and stereoselective conjugate addition of lithium dimethylcopper to an α, β-acetylenic esters and an elaboration of the C 6 -C 7 trans-olefin geometry by a Julia-Kocienski olefination.Macrocyclic marine natural products are a rich sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…For the synthesis of the southern fragment ( 2 ), we needed enantiopure Weinreb amide 8 . Access to an enantiopure precursor of 8 had been developed by Ghosh and Yuan,46 who had employed Amano Lipase PS47 for the enzymatic resolution of the corresponding racemate (Scheme ). In our case, the desired enantiomer was the acetate.…”
Section: Methodsmentioning
confidence: 99%
“…For the synthesis of the southern fragment ( 2 ), we needed enantiopure Weinreb amide 8 . Access to an enantiopure precursor of 8 had been developed by Ghosh and Yuan,46 who had employed Amano Lipase PS47 for the enzymatic resolution of the corresponding racemate (Scheme ). In our case, the desired enantiomer was the acetate.…”
Section: Methodsmentioning
confidence: 99%
“…Amongst, some representative compounds such as; iriomoteolide 1a (accepted ID: CSID17627054), hovenidulcioside A2 (accepted ID: HMDB41029) and ginsenoside F3 (accepted ID: HMDB39556) in the KVA extract; Notoginsenoside I (accepted ID: HMDB31371), ganoderic acid H (accepted ID: HMDB35987) and mibefradil (accepted ID: CSID54673) in the RVA extract; Papulacandin A (accepted ID: CHEBI:72611), 2-palmitoyl-sn-glycero-3-phosphocholine (accepted ID: CSID21403165) and tetra-(3E)-3-hexen-1-yl methylenebis (phosphonate) (accepted ID: CSID4524297) in the NZVA extract, all of them have also been reported to exert the important biological functionalities (e.g., immune activity and disease healing and anti-cancer etc.) in literatures ( Elkhatee et al, 2018 ; Ghosh and Yuan, 2009 ; Zhang and Wang, 2006 ). This study, for the first time, identified and compared the bioactive substances in the VAEs from different countries, and it may be said that all the VAEs studied are rich in the bioactive substances.…”
Section: Resultsmentioning
confidence: 99%
“…It was also noted that some compounds were also found in two different VAE types for instance; 13, 13 and 11 compounds were found in both the KVA and RVA; KVA and NZVA; and RVA and NZVA extracts, respectively. Although the quantifications of the identified compounds were not done, there might be some differences existing in their levels among the three VAE types as shown in CSID54673) in the RVA extract; Papulacandin A (accepted ID: CHEBI:72611), 2-palmitoylsn-glycero-3-phosphocholine (accepted ID: CSID21403165) and tetra-(3E)-3-hexen-1-yl methylenebis(phosphonate) (accepted ID: CSID4524297) in the NZVA extract, all of them have also been reported to exert the important biological functionalities (e.g., immune activity and disease healing and anti-cancer etc.) in literatures (Elkhatee et al, 2018;Ghosh and Yuan, 2009;Zhang and Wang, 2006). This study, for the first time, identified and compared the bioactive substances in the VAEs from different countries, and it may be said that all the VAEs studied are rich in the bioactive substances.…”
Section: Bioactive Compounds Among the Vaesmentioning
confidence: 90%
“…1 Because of the attractive biological profile and the unique structural attributes of iriomoteolide 1a, several laboratories have undertaken the total synthesis of 1 . The groups of Loh, 2 Paterson, 3 Zhao, 4 Li, 5 and Dai 6 have reported creative approaches to complex fragments of 1 , while Horne, 7 Ghosh, 8 and Yang 9 have completed the total synthesis of macrolactone 1. During the course of their synthetic studies, Horne, 7 Ghosh, 8 and Yang 9 independently ascertained that the proposed structure of iriomoteolide 1a had been misassigned.…”
mentioning
confidence: 99%
“…The groups of Loh, Paterson, Zhao, Li, and Dai have reported creative approaches to complex fragments of 1 , while Horne, Ghosh, and Yang have completed the total synthesis of macrolactone 1 . During the course of their synthetic studies, Horne, Ghosh, and Yang independently ascertained that the proposed structure of iriomoteolide 1a had been misassigned (Figure ).…”
mentioning
confidence: 99%